Outcome of Training on “Doctor-Patient Communication Skill” for the Pre-intern Physicians (Journal of Medicine, 2019)
Background: Communication is the way how a physician interacts with the patient; it should have nonverbal, verbal and para-verbal components. This study was designed for communication skill training on newly graduated medical and dental physicians and to compare the outcomes of training in terms of pretest and post-test results among experimental group and control groups.Materials & methods: It was a randomized, prospective, interventional study performed on newly graduated medical and dental physicians, recruited from four participating centres: Chittagong Medical College, Chattagram Maa-O-Shishu Hospital Medical College, Southern Medical College & Hospital and Chattagram International Dental College. Duration of study was from 1st January 2017 to 30th August 2017. After selecting 60 participants (experimental group: 50; control group: 10) by lottery method, informed consent was taken and all the participants of both groups appeared at a pre-test. Only experimental group attended the training program and both the groups appeared at post-test.Results: When pre-test and post-test values of experimental group was compared by t-test, the p values for proper introduction, verbal, non-verbal, para-verbal and total scores were 0.00, 0.00, 0.00, 0.00 and 0.00 respectively. During comparison post-test scores in experimental and control groups by ANCOVA, the p values for proper introduction, verbal, non-verbal, para-verbal and total scores were 0.00, 0.00, 0.00, 0.00 and 0.00 respectively.Conclusions: There was significant improvement in communication skill of physicians after receiving the training with no possibility of occurring those changes by chance. If appropriate, the results can be utilized to approach for formal introduction of communication skills training for pre-intern physicians.J MEDICINE JAN 2020; 21 (1) : 3-7